Penguatan Kesehatan Warga Desa Sungai Petai melalui Inovasi Jamu Instan, Infused Water dan Layanan Pemeriksaan Kesehatan Terpadu - Haiyul Fadhli; Wira Noviana Suhery; Benni Iskandar; Silvana Anggraini; Taqqia Sajja Wanda; Rinta Maspat; deswita Sandra Tsalsabila Ananto; windi Alfayutia (Institut Pertanian Bogor, 2025)
Degenerative diseases such as hypertension, diabetes mellitus, and gout have developed and threaten the quality of life of the community, especially in rural areas. This community service aims to enhance awareness among the residents of Sungai Petai Village about the benefits of instant herbal medicine, infused water, and health education for early detection and maintaining a healthy lifestyle. The method used is service learning with health counseling, demonstration of instant herbal medicine and infused water, and health checks (blood pressure, blood sugar, and uric acid), followed by a pretest and posttest to assess the improvement of health education, with a pretest and posttest to determine the improvement of knowledge. The results showed that the education significantly improved participants' understanding of diseases and health products, with a considerable and sizable overall increase in knowledge at the posttest (80.83). The health check also showed that some participants had health conditions that required further attention.